Arthroscopic Anterior Cruciate Ligament Reconstruction: A Meta-Analysis Comparing Semitendinosus Alone and Semitendinosus with Gracilis Tendon Autografts - Chin, Brian Zhaojie; Wee, Ian Jun Yan; Syn, Nicholas Li-Xun; Krishna, Lingaraj (The Journal of Knee Surgery, 2019)
The objective of this study was to provide a comprehensive systematic review and meta-analysis to compare patient-reported outcomes and functional knee parameters of anterior cruciate ligament (ACL) reconstruction surgery with semitendinosus (ST) and ST-gracilis (G) grafts. This study was conducted according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and Meta-Analysis of Observational Studies in Epidemiology (MOOSE) guidelines. All studies in PubMed and Embase that reported functional knee parameters and patient-reported outcomes after ACL reconstruction with ST and ST-G grafts independently were included in the review. Selected end points for random effects, pairwise meta-analysis included side-to-side deficit (%) in isokinetic peak torque, peak torque ratio (%), side-to-side difference (mm) in anterior laxity, and patient-reported outcome scores at minimum 2-year follow-up. A total of 15 primary references comprising 1,109 participants were identified. The ST group had decreased side-to-side deficit in isokinetic peak torque when compared with the ST-G group for flexion at 60 degrees/s (p = 0.02) and 180 degrees/s (p = 0.01) at 2-year follow-up. There were no significant differences in side-to-side difference in anterior laxity (p = 0.81), hamstring/quadriceps peak torque ratios at 60 degrees/s (p = 0.83) and 180 degrees/s (p = 0.36), and patient-reported outcomes in the International Knee Documentation Committee score (p = 0.06) and Lysholm score (p = 0.67). The addition of the gracilis tendon to the hamstring autograft in ACL reconstruction results in increased side-to-side deficits in isokinetic peak flexion torque. However, patient-reported outcome scores and knee laxity measurements are comparable with those of ST grafts.
Keywords: ACL reconstruction; hamstring graft; patient-reported outcomes